Device optimization for high-performance quantum dot-based light-emitting diodes - Ding, Tao (2018)
Recent two decades have witnessed the burgeoning development of quantum dot-based light-emitting diodes (QLEDs) since its first demonstration in 1994. It has been regarded as one of the next-generation lighting and display technologies, mainly due to the confirmed extraordinary advantages such as tunable wavelength across the whole visible spectrum, narrow full-width at half-maximum (FWHM), superior color saturation feature and economical manufacture accessibility. Although tremendous achievements in this research area have been attained especially in recent two to three years, which have proved its comparable performance with organic LEDs (OLEDs), there still remain some deficiencies yet to be overcome. This thesis will focus on the following topics regarding to the manipulation of carrier injection balance, the replacement of charge injection layers and the realization of full-inorganic prototype QLEDs. First of all, a novel cathode interfacial material (CIM) was introduced to improve the QLED performance by modulating the charge balance. With its promising electron transport behavior and low processing temperature, the resultant devices demonstrate better features in terms of external quantum efficiency (EQE), current (CE) and power efficiencies (PE). Furthermore, by incorporating this CIM with traditional LiF together as the cathode buffering layers, the corresponding device showed superior performance, which could be attributed to the better energy band alignment and more balanced charge injection due to the reduced barrier for electron injection from cathode. Meanwhile, two inorganic materials, sol-gel prepared copper oxide (CuO) and commercially-available copper thiocyanate (CuSCN) were utilized as the replacements for poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS), respectively. For CuO-based QLED, the operation lifetime is enhanced due to the introduction of inorganic hole injection material, while the device performance is comparable with PEDOT:PSS-based ones. Furthermore, an inorganic CuSCN with simpler preparation method was applied, and the turn-on voltage of the corresponding QLED was dramatically decreased due to the better energy band alignment of CuSCN than PEDOT:PSS with comparable device performance. Moreover, in order to further promote the stability of QLEDs, devices using inorganic materials with optimization were proposed with specific design philosophy. By the insertion of thin lithium fluoride (LiF) as the insulating as well as buffering layer, the QD charging and carrier imbalance were suppressed in the operating device, resulting in improved performance with an external quantum efficiency of 1.74% and a maximum brightness over 7,600 cd/m2, which are among the best reported values for all-inorganic QLED to the best of our knowledge. To sum up, this thesis mainly addresses three aspects of the current deficiencies in QLEDs. First, a surpassing charge balance was achieved by the manipulation of cathode buffering layers, demonstrating the feasibility of the CIM in improving the device performance. On the other hand, two alternative inorganic materials have been introduced as the hole injection material for substituting PEDOT:PSS, resulting in improved device operation lifetime and lower turn-on voltage; Furthermore, all-inorganic QLEDs with record performance so far were systematically fabricated with proper device engineering. We firmly believe that the aforementioned demonstrated results enable new guidelines and prospects for the development and growth of QLED community.